2009
DOI: 10.3904/kjim.2009.24.1.48
|View full text |Cite
|
Sign up to set email alerts
|

EGFR and KRAS Mutations in Patients With Adenocarcinoma of the Lung

Abstract: Background/Aims Mutations of the epidermal growth factor receptor (EGFR) and Kirsten rat sarcoma viral oncogene (KRAS) are important in the pathogenesis of lung cancer, and recent reports have revealed racial and geographical differences in mutation expression. Methods This study was conducted to investigate the prevalence of EGFR and KRAS mutations and their correlation with clinical variables in Korean patients with adenocarcinoma of the lung. Formalin-fixed adenocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
25
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 24 publications
8
25
2
1
Order By: Relevance
“…This observation is consistent with other studies showing that the frequencies of KRAS mutations vary with ethnicity [77][78][79][80] . G12D was the most frequent KRAS transition mutation found …”
Section: Dependency Of Ral Activity On Ras Mutationsupporting
confidence: 82%
“…This observation is consistent with other studies showing that the frequencies of KRAS mutations vary with ethnicity [77][78][79][80] . G12D was the most frequent KRAS transition mutation found …”
Section: Dependency Of Ral Activity On Ras Mutationsupporting
confidence: 82%
“…Recently, it was found that EGFR mutation was a sensitive marker of NSCLC to EGFR TKI drugs, while KRAS mutation was a resistant one [22,23]. Considering the incidence of gene mutations including EGFR and KRAS in NSCLC varied regionally and racially, we detected EGFR and KRAS mutations in 157 NSCLC patients from mainland China, and found that the mutation frequencies of EGFR and KRAS were both similar to reports from other East Asia areas, such as Taiwan China, Japan and Korea [19,[24][25][26][27][28]. Comparing to western countries, the mutation frequency of EGFR was higher, while that of KRAS was lower in the East Asia areas [20,29,30].…”
Section: Discussionmentioning
confidence: 70%
“…EGFR mutations were also reported in rarely seen types of NSCLC such as pleomorphic (15%), and also adenosquamous carcinomas (38%) (Jia and Chen, 2011;Lee et al, 2011). A South Korean study detected EGFR mutations in 24% of the cases with adenocarcinomas (Jang et al, 2009). EGFR mutations were also found in 9 of 33 cases with sarcomatoid carcinoma which is a rarely seen subtype (Jiang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%